Childhood Education and Popular Islam: Islamic Psychology as a Pattern of Early Childhood Education in the Authoritative Affinity of Popular Islam - Ahnan 'Azzam, Dimas; Leany, Muhammad (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2024)
Purpose – This study examines how Islamic psychology contributes to early childhood education by integrating spirituality, emotional well-being, and intellectual development, while addressing the impact of globalization and popular Islam on the authenticity of Islamic teachings. Design/methods/approach – The study employs a qualitative methodology centered on conceptual analysis, utilizing systematic reviews of scholarly articles, books, and relevant media. This approach critically examines key concepts such as fitrah (innate nature), nafs (soul dynamics), and their applications in early childhood education, particularly in the context of media and cultural globalization. Findings – The findings reveal that Islamic psychology provides a robust foundation for addressing contemporary challenges in early childhood education. Key principles such as fitrah and tawhid support the development of children’s spiritual, cognitive, and emotional capacities. However, the increasing commercialization of Islamic values through popular media risks diluting these teachings into superficial symbols. The study emphasizes the need for parental and educator involvement to ensure the alignment of popular Islamic content with authentic religious values, providing a balanced approach to moral and spiritual education. Additionally, the research highlights the potential of Islamic psychological principles to offer innovative solutions to counteract identity crises in children, promoting resilience against the influences of globalization and consumer culture. Research implications/limitations – The study is limited to theoretical and conceptual analyses of Islamic psychology in early childhood education and does not include empirical data. Future research should focus on field-based studies to evaluate the practical application of these concepts in diverse cultural and educational settings. Additionally, the findings underscore the necessity for policy reforms to integrate Islamic psychological principles into early childhood education curricula. Practical implications – This research provides actionable insights for integrating Islamic psychology into early childhood education by combining spiritual, cognitive, and emotional development, leveraging media responsibly, and creating Islamic value-oriented environments to help children navigate sociocultural challenges while maintaining their religious identity. Originality/value – This study highlights the integration of Islamic psychological principles to address challenges in early childhood education amid popular Islam and globalization, offering a holistic paradigm that balances intellectual, spiritual, and emotional development to create resilient, morally grounded individuals. Paper type Conceptual paper